Calculation and Analysis of Critical Speed of High-speed Gear Rotor based on Romax - Jizhe Mao; Yongchao Yuan; Yanjun Cao; Kun Zhang; Li Yu; Haiming Gang (Jixie chuandong)
The high speed gear rotor is widely used， and its dynamic property affects the stability and reliability of gearbox. The dynamic analysis of two kinds of high-speed gear rotor with abnormal vibration are proceeded by Romax software， the each nature frequency of two rotors and the influence of the bearing supporting parameter on each nature frequency are obtained. It is found that the running speed of first two high speed gear rotor before improvement is approached to the first order critical speed. At the same time， the shaft system structure is improved in the Romax to make sure the running speed faraway from critical speed. The improved test result indicates that the each vibration index is normal， and the running condition of gearbox is pretty well. A method for accurate calculating the critical speed of high-speed gear rotor is provided.